Forecasting and material requirements planning / Noor Izah Ismail - Ismail, Noor Izah (Universiti Teknologi MARA Cawangan Pahang, 1989)
"Forecasting is· a process of estimating a future event by casting forward past data. The past data are systematically combined in a predetermined way to obtain the estimate of the future"1. Forecasting is subphase of planning. In a management process, planning, organizing, and controlling are not independent processes, rather they interrelate and overlap. However, if operations are properly planned and organized, control would be smoother and easier. Forecasting, when introduced, can reduce the costs of readjusting operations in response to unexpected deviations by specifying future demand. Therefore, if the planning process is well conceived and actual production is effectively and efficiently carried out, there is a likelihood of high productivity. On the other hand, if the forecast has considerable error, even a well conceived plan and an excellent operating performance may result in a disappointing productivity. In a production system, one of the ways to achieve productivity is the use of Material Requirements Planning.